2009
DOI: 10.5194/angeo-27-1789-2009
|View full text |Cite
|
Sign up to set email alerts
|

Cluster and ACE observations of phase synchronization in intermittent magnetic field turbulence: a comparative study of shocked and unshocked solar wind

Abstract: Abstract. We apply two distinct nonlinear techniques, kurtosis and phase coherence index, to analyze the modulus of interplanetary magnetic field data |B| measured by Cluster and ACE spacecraft from 1 to 3 February 2002. High degree of phase synchronization is found across a wide range of time scales, from 1 s to 10 4 s, in the magnetic field fluctuations, both in the shocked solar wind upstream of Earth's bow shock and in the unshocked ambient solar wind at the L1 Lagrangian point. This is the first direct me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 54 publications
(87 reference statements)
1
46
0
Order By: Relevance
“…The aforementioned studies on Alfvén chaos elucidate how Alfvén intermittency appears in space and astrophysical plasmas, such as the magnetic intermittent turbulence observed in the solar wind (Koga et al, 2007;Sahraoui, 2008;Chian and Miranda, 2009;Chian and Muñoz, 2011), due to nonlinear dynamical phenomena such as the type-I intermittency induced by a saddle-node bifurcation, the crisisinduced intermittency induced by an interior crisis, and the extrinsic intermittency induced by a noise (Hada et al, 1990;Chian et al, 1998Chian et al, , 2006Chian et al, , 2007Rempel et al, 2006Rempel et al, , 2008Sánchez-Arriaga et al, 2009;Miranda et al, 2012).…”
Section: Jatenco-pereira Et Al: Alfvén Waves In Dusty Plasmasmentioning
confidence: 99%
“…The aforementioned studies on Alfvén chaos elucidate how Alfvén intermittency appears in space and astrophysical plasmas, such as the magnetic intermittent turbulence observed in the solar wind (Koga et al, 2007;Sahraoui, 2008;Chian and Miranda, 2009;Chian and Muñoz, 2011), due to nonlinear dynamical phenomena such as the type-I intermittency induced by a saddle-node bifurcation, the crisisinduced intermittency induced by an interior crisis, and the extrinsic intermittency induced by a noise (Hada et al, 1990;Chian et al, 1998Chian et al, , 2006Chian et al, , 2007Rempel et al, 2006Rempel et al, , 2008Sánchez-Arriaga et al, 2009;Miranda et al, 2012).…”
Section: Jatenco-pereira Et Al: Alfvén Waves In Dusty Plasmasmentioning
confidence: 99%
“…Figure 1a shows the time series of the modulus of magnetic field |B| obtained by the FGM instrument onboard Cluster-1 (Balogh et al, 2001) from 00:00 to 12:00 UT on 2 February 2002. During this interval Cluster-1 was in the solar wind upstream of the Earth's bow shock (Chian and Miranda, 2009). The magnetic field data are collected by Cluster-1 at a resolution of 22 Hz (Balogh et al, 2001).…”
Section: Data Analysis Toolsmentioning
confidence: 99%
“…The probability distribution functions (PDFs) of turbulent space plasmas display sharp peaks and fat tails on small scales within the inertial subrange (Sorriso-Valvo et al, 2001;Bruno et al, 2001;Koga et al, 2007;Chian and Miranda, 2009), as well as departures from self-similarity and monofractality (Bershadskii and Sreenivasan, 2004;Bruno et al, 2007;Miranda et al, 2013). These features are due to the presence of rare, large-amplitude coherent structures which dominate the statistics of fluctuations on small scales and can be quantified by the computation of statistical moments.…”
Section: Introductionmentioning
confidence: 99%
“…The link between non-Gaussianity and phase synchronization in intermittent turbulence was established by Koga et al (2007) using the Geotail magnetic field data upstream and downstream of the Earth's bow shock. The phase coherence surrogate technique was used to study phase synchronization in magnetic field data from Cluster in the magnetosheath close to the Earth's magnetopause (Sahraoui et al, 2008), in plasma density fluctuations observed by SOHO image in the solar corona (Telloni et al, 2009) and in magnetic field data both in the shocked solar wind measured by Cluster upstream of the Earth's bow shock and in the unshocked ambient solar wind measured by ACE at the L1 Lagrangian point (Chian & Miranda, 2009 In this paper, we study the scale dependence of kurtosis and phase coherence in intermittent magnetic field turbulence measured at three different locations of the solarterrestrial environment: (1) in the solar photosphere, (2) in the solar wind, and (3) on the ground. We investigate two scenarios: a non-ICME event in February 2002 and an ICME event in January 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The active region, on the other hand, displays an increase of kurtosis as the spatial scale r decreases, which is a characteristic of a non-Gaussian process related to nonlinear energy cascade within the inertial subrange, and these values are higher than those obtained from the quiet region for scales < ∼20 pixels ∼ 29 Mm. The degree of phase synchronization measured by the phase coherence index (Hada et al, 2003;Koga et al, 2007;Chian & Miranda, 2009) in the active region increases with decreasing spatial scale r, while the quiet region presents low-degree of synchronization at all scales. Note that at large scales the lack of datapoints introduces big errors in the computation of the phase coherence index.…”
mentioning
confidence: 99%